Prognostic value of liver fibrosis and steatosis biomarkers in type‐2 diabetes and dyslipidaemia. Issue 9 (3rd September 2014) - Perazzo, H.; Munteanu, M.; Ngo, Y.; Lebray, P.; Seurat, N.; Rutka, F.; Couteau, M.; Jacqueminet, S.; Giral, P.; Monneret, D.; Imbert‐Bismut, F.; Ratziu, V.; et al.
Summary Background In cardiometabolic disorders, non‐alcoholic fatty liver disease is frequent and presumably associated with increased mortality and cardiovascular risk. Aim To evaluate the prognostic value of non‐invasive biomarkers of liver fibrosis (FibroTest) and steatosis (SteatoTest) in patients with type‐2 diabetes and/or dyslipidaemia. Methods A total of 2312 patients with type‐2 diabetes and/or dyslipidaemia were included and prospectively followed up for 5–15 years. The cardiovascular Framingham‐risk score was calculated; advanced fibrosis and severe steatosis, were defined by FibroTest >0.48 and SteatoTest >0.69, respectively, as previously established. Results During a median follow‐up of 12 years, 172 patients (7.4%) died. The leading causes of mortality were cancer (31%) and cardiovascular‐related death (20%). The presence of advanced fibrosis [HR (95% CI)] [2.98 (95% CI 1.78–4.99); P < 0.0001] or severe steatosis [1.86 (1.34–2.58); P = 0.0002] was associated with an increased risk of mortality. In a multivariate Cox model adjusted for confounders: the presence of advanced fibrosis was associated with overall mortality [1.95 (1.12–3.41); P = 0.02]; advanced fibrosis at baseline [n = 50/677; 1.92 (1.04–3.55); P = 0.04] and progression to advanced fibrosis during follow‐up [n = 16/127; 4.8 (1.5–14.9); P = 0.007] were predictors of cardiovascular events in patients with type‐2 diabetes. In patients with a Framingham‐risk score ≥20%, the presence of advanced fibrosis was predictive of cardiovascular events [2.24 (1.16–4.33); P < 0.05]. Conclusions Liver biomarkers, such as FibroTest and SteatoTest, have prognostic values in patients with metabolic disorders. FibroTest has prognostic value for predicting overall survival in patients with type‐2 diabetes and/or dyslipidaemia. In type‐2 diabetes, FibroTest predicted cardiovascular events and improved the Framingham‐risk score.